Tree diversity, structure and composition in coffee agroforestry with varying shade systems, coffee species, and landscape settings in Malang, Indonesia - LUCHMAN HAKIM; MUHAMMAD YUSUF; FITRA D. WIRATANTRA; BRIAN RAHARDI; WENNY B. SUNARHARUM; AGUS NURROFIK (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Hakim L, Yusuf M, Wiratantra FD, Rahardi B, Sunarharum WB, Nurrofik A. 2026. Tree diversity, structure and composition in coffee agroforestry with varying shade systems, coffee species, and landscape settings in Malang, Indonesia. Biodiversitas 27 (5): d270509. https://doi.org/10.13057/biodiv/d270509. Coffee agroforestry in Malang Region, East Java, Indonesia has been widely recognized as a multifunctional land-use system that integrates economic, and social benefits; however, its comprehensive ecological characteristics remain poorly documented. This study examines tree diversity and ecological indicators in coffee agroforestry systems in Malang, East Java, across four landscape settings, three coffee species (arabica, robusta, and liberica) and shade systems typology (shaded monoculture, commercial polyculture, traditional polyculture and rustic). Field surveys were conducted at 64 sites to document shade-tree diversity, composition (Important Value Index) and ecological indices (Shannon-Wiener Diversity Index (H′), Evenness Index (E), and Simpson Dominance Index (D′)). In total, there were 40 species of shade trees across all sites and primarily composed of Fabaceae and Malvaceae which contribute to soil fertility, habitat provision, and raw material resources. Results indicated that among shaded systems in averages includes, rustic-type exhibited the highest tree species diversity, high evenness, and low dominance (H′ = 2.02, E = 0.97, D = 0.19), followed by traditional polyculture systems (H′ = 1.23, E = 0.91, and D = 0.3), commercial polyculture (H′ = 0.8, E = 0.89, D = 0.46), and shaded monoculture (H′ = 0.17, E = 0.29, and D = 0.83). Liberica coffee agroforestry tended to show higher diversity index of shade trees with less dominance of few species compared to the other two. However, although its diversity assessments belong low to moderate scores, the presence of shade tree diversity has been shown to have a practical impact on the dynamics of coffee agroforestry, allowing farmers to increase food security while generating additional income beyond coffee. Therefore, to support ecological sustainability and community well-being in the Malang Region, conservation strategies and policy frameworks should prioritize biodiversity-friendly agroforestry management.